Quantitative B and T cell abnormalities in four patients presenting with mucormycosis and prior asymptomatic COVID-19 infection. Issue 8 (9th August 2022) - Mandke, Charuta; Divekar, Rohit; Pradhan, Vandana; Arora, Shitij
Abstract : India saw an unprecedented and rapid rise of invasive coronavirus-associated mucormycosis (CAM) during the delta COVID-19 surge. There is little known about the pathophysiology and if there is a direct causation between the COVID-19 infection and invasive CAM. While the traditional risk factors such as uncontrolled diabetes and other immunocompromising conditions are recognised, there could be several COVID-19-induced phenomena that may predispose the patients to develop CAM and are yet unrecognised. It has been proposed that prior severe COVID-19 is associated with invasive CAM. This could be due to the increased use of immunomodulators or the direct effects of the COVID-19 infection. We report four patients with CAM during the delta surge who did not have prior known COVID-19 infection but on subsequent testing had positive antibodies suggesting past asymptomatic infection. We report the quantitative abnormalities in lymphocyte subsets in all four patients and report CD19+ B cell lymphopenia and reduced percentage of CD27+ CD45RA+ naïve helper T cells. CAM may occur in patients after asymptomatic COVID-19 infection, in the absence of systemic corticosteroid and immunomodulator use, and may reflect underlying immune abnormalities possibly attributable to or unmasked by prior COVID-19 infection.